Considering different streamflow forecast horizons in the quantitative flood risk analysis for a multi-reservoir system. (December 2020) - Gong, Yu; Liu, Pan; Zhang, Jun; Liu, Dedi; Zhang, Xiaoqi; Zhang, Xiaojing
Highlights: Different forecast horizons are considered to quantify multi-reservoir flood risk. The multinormal distribution of multi-reservoir storage is deduced. Joint effective forecast horizons are captured with minimum flood risk. Abstract: The flood risk analysis of a multi-reservoir system is based on the forecasted streamflow, whose time length is the forecast horizon (FH). FHs are generally different for each reservoir while the operation horizon (OH) is the same in a multi-reservoir system. To bridge the gap between the FHs and the OH of the multi-reservoir system, this study aims to develop a two-stage flood risk analysis method, specifically considering different FHs of each reservoir. In the first stage (the time period within the FHs), multinormal distribution of multi-reservoir storage was deduced by using the multivariate autoregressive model. In the second stage (the time period between the FHs and the OH), flood risk was calculated by using the reservoir routing for design flood hydrographs. The total flood risk within the OH incorporated the risks in the first and second stages. Finally, the joint effective FHs corresponding to the minimum total flood risk could be identified by numerical experiments. The results for the case study indicate that: (1) the proposed two-stage flood risk analysis utilizes different FHs in the multi-reservoir system and bridge the gap between the FHs and the OH; (2) the joint effective FHs are not constants and change with inflow conditions.